THE INFLUENCE OF HALAL LABELS, INCOME, PRODUCT INGREDIENTS, AND LIFESTYLE ON CONSUMER PURCHASE INTEREST IN IMPORTED KOREAN COSMETIC PRODUCTS IN GENERATION Z - Norma Rosyidah (Journal of Halal Lifestyle and Sustainability, 2025)
Teenagers prefer the current trend of Korean style, so many Indonesian companies are rushing to create products that meet the community's needs and compete with foreign companies. In addition, companies are more focused on their preferences, forgetting the fact that Indonesians also need halal product labels. However, the lack of halal awareness (consumer knowledge about halal products) makes Indonesians forget the importance of halal-labeled products. This study aims to investigate the impact of halal labels, income, product ingredients, and lifestyle on the purchasing interest of Gen Z consumers in imported Korean cosmetics. This study uses a quantitative research method. This study demonstrates validity in several tests. It also provides additional information, references, and insights for readers regarding the influence of halal labels, product ingredients, and lifestyle on the interest of Gen Z consumers in purchasing imported Korean cosmetics. It can also help companies understand the extent to which halal labels influence consumers, including their product preferences and lifestyle, as well as their interest in purchasing cosmetics imported from Korea.